2019
DOI: 10.1021/acs.jpcc.9b03903
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfinement Effect on n-Alkane Flow

Abstract: Nanoconfinement induces change of microscopic structures of n-alkanes, which, in turn, alters their dynamics. We study a fundamental question of nanoscale n-alkane flow through in-depth theoretical analysis of relating microscopic structures to macroscopic dynamic properties. We show that the velocity profile and corresponding flux are governed by the interfacial resistance from first-layer n-alkanes near a nanopore wall and the viscous resistance from other n-alkanes in nanopores. We find that n-alkane flow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…The diffusion of hydrocarbons within kerogen pores is essential for shale gas transport. Collell et al studied the light hydrocarbon diffusion behavior in type II kerogen, and the results indicated that as the molecular weight increases, the diffusion coefficient decreases. The light hydrocarbon diffusion coefficient in kerogen is one order of magnitude lower than that in bulk.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion of hydrocarbons within kerogen pores is essential for shale gas transport. Collell et al studied the light hydrocarbon diffusion behavior in type II kerogen, and the results indicated that as the molecular weight increases, the diffusion coefficient decreases. The light hydrocarbon diffusion coefficient in kerogen is one order of magnitude lower than that in bulk.…”
Section: Introductionmentioning
confidence: 99%
“…With the inorganic (quartz) surface energy equal to 61.24 mJ/m, 2,73,74 l o = 0.19 nm and μ oeff = 8.53μ bo for C 8 H 18 are used in this study. 34 Due to the entrance effect, an additional pressure drop Δp ent caused by an extra hydrodynamic resistance is introduced for the flow in a cylindrical pore 40,75…”
Section: Introductionmentioning
confidence: 99%
“…For the oil phase, Wu et al studied the nanoconfinement effect on n -alkane flow behaviors and the results showed that the interfacial oil viscosity governed the velocity. They also found the dependence of the interfacial n -alkane viscosity on the nanopore wall energy and the length of n -alkane . With the oil/water system in the inorganic nanopores, the viscosity of the interfacial water/oil phase can be several times smaller or greater than that of the bulk water/oil phase; therefore, the complex and diverse interfacial fluid viscosity would affect the imbibition behaviors strongly and should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, validation of this extension is in need because the structure of oil components, like n-alkanes, is very different from water. Recently, based on the different mobility between the first-layer molecules and those in the bulk, Wu et al (2019) derived the slip length when n-alkanes flow in nanotubes. However, parameters in their equations, like natural relaxation time, are difficult to determine.…”
Section: Introductionmentioning
confidence: 99%